Sick society - Nizama-Valladolid, Martín (2015)
While advances in various areas of human knowledge have allowed a great development in many areas of life in postmodern society ; on the other hand there is a global trend towards extreme individualism ; family anomie ; corruption and social violence; issues that compromiso much of the population; significantly increasing the risk of mental health disorders or worsen existing one’s. This morbid reality presents multifactorial etiology ranging from alterations in the genome to dysfunctional social factors and the complex interaction of both. The impact is observed in the individual; family and social environment; such condition being perpetuated by a overpowerd State; anethical medias and Thanatical culture; whose components are hedonism; debauchery and compulsive connectivity. Finally; from a holistic perspective; some alternatives are formulated in order to control or reduce such mismatches.